A comparison of students’ interest in STEM across science standard types - Brienne K. May; Jillian L. Wendt; Michelle J. Barthlow (Social Sciences and Humanities Open, 2022)
This study aimed to determine whether science standard type had a significant impact on student interest in science, technology, engineering, math, and overall STEM. The study was conducted with a sample population of ninth and tenth grade students in Pennsylvania enrolled in science classes at school districts implementing the Next Generation Science Standards (NGSS) or the traditional Pennsylvania science standards. The study also focused on the differences between male and female interest in STEM. The Science Technology Engineering and Math Career Interest Survey (STEM-CIS), a Likert-style survey, was digitally administered to participants and a MANOVA was utilized to compare mean scores on the instrument subscales and overall scores. The results showed a statistically significant difference in science and technology subtest scores and for the overall STEM score based on standard type. There was no statistically significant difference in the interest in STEM overall between male and female participants when analyzed based on standard type. Implications for practice and suggestions for future study are offered.